Ringerz / Nurul Asnida Mohd Habibullah - Mohd Habibullah, Nurul Asnida (2020)
Nowadays, people are concerning about any missing key or important items and it which wastes a lot of time and can interrupt your day. Our Ringerz will provide a keychain that has features like ringer to track any missing key or important items to ensure it's found quickly. We can save a lot of time and feel less stressful especially to working people or those with memory problems associated with Alzheimer's disease or problems paying attention typical of attention deficit hyperactivity disorder (ADHD). The simple and classy design, thin, and lightweight and discreet colours of Ringerz make it very suitable to match with anything such as car key, house key, remote control, luggage, and even the wallet. It operates up to 160 feet, and the battery lasts 18 months. No setup or programming is required, and the company provides a 1 year warranty. The main reason that makes this keychain so functional is this keychain will help people by make loud noises every time they hit the control button. They can do it continuously until they find the lost item, which makes the entire searching process super easy. The keychain also features a powerful LED light for more visibility in the dark, and a sturdy outer shell that ensures a long lifespan. There will have a variety of designs according to customers demand. We will introduce this new technology to public, in order to reduce some stressful feeling and waste a a lot of time searching for the missing key. This keychain made of polycarbonate plastic which make it more durable. This keychain will be controlled by using the app. The app will triggered an alarm if the Ringerz is on for 2 days without connected to the device. This is to provide anti theft system to the Ringerz. This Ringerz has functions and advantages not found in today's common ringing keychain, thus providing a competitive advantage over more established competitors. The price is reasonable and there is no physical energy used. Our company target for production in first year we will target RM169,920,000. The management team in our company consist of several sections and is conducted by experienced employee to make sure our company is run efficiently.